How solve equation arctg1+arctg2+arctgx=pie?

### 1 Answer | Add Yours

We have

`tan^(-1)x+tan^(-1)y=tan^(-1)((x+y)/(1-xy))`

Apply this formula

`tan^(-1)1+tan^(-1)2+tan^(1)x`

`=tan^(-1)((1+2)(1-1xx2))+tan^(-1)x`

`=tan^(-1)(3/(1-2))+tan^(-1)x`

`tan^(-1)(-3)+tan^(-1)x=tan^(-1)((-3+x)/(1-(-3)x))`

`=tan^(-1)((x-3)/(1+3x))`

`Thus`

`tan^(-1)((x-3)/(1+3x))=pi`

`(x-3)/(1+3x)=tan(pi)`

`(x-3)/(1+3x)=0`

`=> x-3=0`

`=>x=3`

ans.

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes